HIGH STRENGTH CONCRETE FILLED SQUARE AND CIRCULAR STEEL TUBES UNDER AXIAL LOAD - Aznan, I.; Narayanan, S.P; Kurian, V.J. (10th International Conference On Concrete Engineering and Technology, CONCET’09, 2009)
Concrete Filled Steel Tube (CFST) is a composite structural system based on filling steel tubes with concrete. Steel and concrete have different stress-strain curves and distinctly different behaviour. The two materials interact and the determination of combined properties is difficult. The compression behaviour of CFST with ordinary concrete and steel has been well studied. However the behaviour of CFST with high strength concrete under axial load and its relevance to offshore applications has not been studied. Hot-rolled welded steel pipes Class Light BS 1387:1985 and cold rolled Square Hollow Section (Grade A) ASTM A 500 were used in a series of axial compression tests. Hollow square and circular CFST specimens and also CFST were tested under axial load to identify the effect of various parameters on the behaviour. 36 specimens were tested with concrete strengths of 30, 60 and 80 N/mm2. The effect of tube thickness, diameter, grade of concrete, stiffening of steel due to infill and the confinement of concrete are examined. Experimental column strengths are compared with the values predicted by Eurocode 4, ACI, AIJ, AS and BS 5400 codes. Small circular CFST are largely affected with steel confinement effect and scale effect. For smaller D/t ratio, a steel tube provides good confinement effect to concrete. For Square CFST with large B/t ratio, it is necessary to take into consideration a capacity reduction due to local buckling of the steel tube wall of the column.